2012
DOI: 10.1186/1756-0500-5-454
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and urinary tract pathogenic infections among HIV seropositive patients at the Komfo Anokye Teaching Hospital in Ghana

Abstract: BackgroundGastrointestinal and urinary tract pathogenic infections are aggravating the incidence and progression of the Human Immunodeficiency Virus (HIV) infection into Acquired Immune Deficiency Syndrome (AIDS) more especially in the developing countries. This study was conducted to assess the common gastrointestinal and urinary infections among HIV/AIDS patients at the Komfo Anokye Teaching Hospital (KATH) in Ghana between April and December 2008.FindingsThis work reports on gastrointestinal and urinary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
4
18
4
Order By: Relevance
“…7 Similarly, G. intestinalis has been described as the most prevalent parasitic fecal pathogen in HIV-infected patients from urban Ghana (19%) regardless of their immune or cART status. 8 In other African series, giardiasis prevalence is higher in HIV versus non-HIV-infected individuals and is more common without cART and ≤ 200 CD4 + T cells/mm 3 . 9 Poor water sanitation, lack of personal hygiene, the presence of other family members infected with G. intestinalis, and oro-anal sexual practices are recognized as risk factors for its acquisition.…”
Section: Discussionmentioning
confidence: 90%
“…7 Similarly, G. intestinalis has been described as the most prevalent parasitic fecal pathogen in HIV-infected patients from urban Ghana (19%) regardless of their immune or cART status. 8 In other African series, giardiasis prevalence is higher in HIV versus non-HIV-infected individuals and is more common without cART and ≤ 200 CD4 + T cells/mm 3 . 9 Poor water sanitation, lack of personal hygiene, the presence of other family members infected with G. intestinalis, and oro-anal sexual practices are recognized as risk factors for its acquisition.…”
Section: Discussionmentioning
confidence: 90%
“…Similar results were reported by Brown et al [29] in a study of HIV-positive pregnant women in Kenya. In Ghana, Boaitey et al (2012) [30] reported that 35% of 500 HIV-positive individuals carried gastrointestinal parasites Giardia lamblia and Cryptosporidium, compared to 4.3% of HIV-negative individuals, underscoring the vulnerability of HIV-positive pregnant women to opportunistic parasites in general. Their study also demonstrated that of the 258 HIVpositive patients who presented with diarrhea and fever, 60 (23.3%) had bacteriuria with predominantly E. coli and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…attracts attention with large epidemics in industrialized countries while being undiagnosed and neglected in many developing countries [ 1 , 2 ]. Cryptosporidiosis is an opportunistic infection in immune-compromised patients, which may results in severe and life-threatening diarrhoea [ 3 5 ]. In immunocompetent hosts the disease is usually self-limited, however it has been shown to induce weight loss, growth stunting, sustained impact on child development and increased case fatality [ 2 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular-typing showed species and subtype specific reservoirs, as well as differences, in terms of diarrhoea manifestation, growth faltering and seasonality [ 12 , 13 , 24 26 ]. Cryptosporidiosis has been recognised as an important cause for childhood diarrhoea in Ghana [ 5 , 10 ]. Nevertheless, no further molecular studies have been performed in Ghana or its neighbouring countries.…”
Section: Introductionmentioning
confidence: 99%